Proceedings of the 7th International Conference on Emerging Databases Technologies, Applications, and Theory (Lecture Notes in Electrical Engineering,, 2018)
This proceedings volume presents selected papers from the 7th International Conference on Emerging Databases: Technologies, Applications, and Theory (EDB 2017), which was held in Busan, Korea from 7 to 9 August, 2017. This conference series was launched by the Korean Institute of Information Scientists and Engineers (KIISE) Database Society of Korea as an annual forum for exploring novel technologies, applications, and research advances in the field of emerging databases. This forum has evolved into the premier international venue for researchers and practitioners to discuss current research issues, challenges, new technologies, and solutions.